Understanding the relations between exposure to the positive self-portrayals of others on social media and emerging adults’ mental health during a COVID-19 imposed lockdown - Ilse Vranken; Lara Schreurs; Edward John Noon; Laura Vandenbosch (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2023)
Social media fulfil emerging adults’ self-presentation needs, and young people often selectively present positive self-portrayals on social media (i.e., exciting social life, successful professional life, and being happy). Yet, being exposed to the positive self-portrays of others can sometimes relate to mental health pressures. In exceptional times of social deprivation (e.g., the COVID-19 pandemic), such relations may differ. This cross-sectional study among 415 emerging adults (Mage = 24.27, SD = 3.19; Women = 64.10%) examined the interrelations between exposure to the positive self-portrayals of others on social media and mental health during an intense COVID-19 lockdown period. The study revealed that exposure to such content related to lower levels of mental health. No support emerged for the moderating role of experiencing negative life events, specifically the experience with COVID-19 illnesses in one’s environment, or a three-way interaction with such experience and gender. These results provide evidence to suggest that specific social circumstances may lead exposure to positive self-portrayals on social media to relate to lower mental health. Specifying such circumstances can help the field to move away from the current inconsistent findings concerning social media/mental health relations.